Cutthroat Capitalism versus Cuddly Socialism: Are Americans more Meritocratic and Efficiency-Seeking than Scandinavians? - Ingvild Almås; Alexander W. Cappelen; Bertil Tungodden (Center for Economic Studies and ifo Institute (CESifo), 2016)
There is a striking difference in income inequality and redistributive policies between the United States and Scandinavia. To study whether there is a corresponding cross-country difference in social preferences, we conducted the first large-scale international social preference experiment, with nationally representative samples from the United States and Norway. We introduce a new experimental approach, which combines the infrastructure of an international online market place and the infrastructure of a leading international data collection agency. A novel feature of our experiment is that Americans and Norwegians make real distributive choices in identical situations where they have complete information about the source of inequality and the cost of redistribution. We show that Americans and Norwegians differ significantly in fairness views, but not in the importance assigned to efficiency. The study also provides robust causal evidence of fairness considerations being much more fundamental for inequality acceptance than efficiency considerations in both countries.
Keywords: 330